2015
DOI: 10.1111/dth.12259
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of a linoleic acid-ceramide containing moisturizer exhibit therapeutic and preventive benefits for psoriasis vulgaris: a randomized controlled trial

Abstract: Psoriasis is a chronic skin inflammatory disorder with frequent relapse. Ceramides and their key enzymes are deficient in the lesions, resulting in impaired epidermal permeability barrier, which correlates with disease severity. We evaluated the efficacy of linoleic acid-ceramide moisturizer (LA-Cer) as an adjunctive and preventive therapy for psoriasis vulgaris. 106 patients were randomized into two groups. The control group (C1 ) received Mometasone Furoate 0.1% Cream (MF) while the treatment group (T1 ) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 71 publications
3
34
0
1
Order By: Relevance
“…Lifetime prevalence of hand eczema was 9.7% (63/650). Prevalence of hand eczema did not differ significantly between genders in this cohort although female dominance has been documented [3,14]. Characteristics of these cohorts are summarized in Table 1.…”
Section: Basic Characteristics Of Subjectsmentioning
confidence: 74%
See 2 more Smart Citations
“…Lifetime prevalence of hand eczema was 9.7% (63/650). Prevalence of hand eczema did not differ significantly between genders in this cohort although female dominance has been documented [3,14]. Characteristics of these cohorts are summarized in Table 1.…”
Section: Basic Characteristics Of Subjectsmentioning
confidence: 74%
“…In both adults and children with atopic dermatitis, TEWL rates positively correlate with disease severity [35][36][37]. Moreover, measurement of TEWL rates is a reliable approach to evaluate the therapeutic efficacy of the treatments for both atopic dermatitis and psoriasis [2,3,38]. In addition, infants with higher TEWL rates during the first week of life predict a higher risk of atopic dermatitis later in the life independently of filaggrin mutations [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14,22 Previous studies have found that topical application of linoleic acid and/or linoleic acid can restore the permeability barrier and improve skin appearance. [23][24][25] Therefore, sacha inchi oil might be an alternative source of essential fatty acids for improvement of skin appearance and function through topical administration. with the fresh skin tissue according to the H&E staining results ( Figure 1A).…”
Section: Fatty Acid Composition and Physicochemical Characteristicsmentioning
confidence: 99%
“…Ceramides are sphingolipids which are of major importance for the homeostasis of the stratum corneum. Among the various ceramides, it is predominantly the linoleic acid containing ceramide I, which is crucial for the stratum corneum integrity (Liu, Xia, Chen, Xue, & Zheng, 2015).…”
mentioning
confidence: 99%